Lithopedion in a Geriatric Patient - Andrés Ricaurte Sossa; Henry Bolaños; Andrés Ricaurte Fajardo; Ángela Camila Burgos; Valentina Garcia; Paola Muñoz; Diego Rosselli (Revista Brasileira de Ginecologia e Obstetrícia, 2019)
Abstract Lithopedion (lithos = rock and paidion = child) is a rare condition that only occurs in 1.5 to 1.8% of extrauterine pregnancies and in 0.00045% of all pregnancies. It consists of an ectopic pregnancy in which the fetus dies but cannot be reabsorbed by the mother’s body, which then coats it in a calcium-rich substance.We present the case of a 77-year-old woman with an incidental diagnosis of a lithopedion, which had been retained in her left pelvis for presumably 40 years.